Burden, etiology, and risk factors of respiratory virus infections among symptomatic preterm infants in the tropics : a retrospective single-center cohort study - Yeo, Kee Thai (2020)
The burden of respiratory viral infections (RVIs) among preterm infants in the first few years of life, especially those living in the tropics with year-long transmissions of respiratory viruses, remains unknown. We aimed to describe the clinical epidemiology and associated risk factors for RVIs among symptomatic preterm infants ≤32 weeks up to 2 years of life.